2013
DOI: 10.1002/jbm.b.32902
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of highly cross‐linked polyethylene wear debrisin vivo

Abstract: Despite the widespread implementation of highly cross-linked polyethylene (HXLPE) liners to reduce the clinical incidence of osteolysis, it is not known if the improved wear resistance will outweigh the inflammatory potential of HXLPE wear debris generated in vivo. Thus, we asked: What are the differences in size, shape, number, and biological activity of polyethylene wear particles obtained from primary total hip arthroplasty revision surgery of conventional polyethylene (CPE) versus remelted or annealed HXLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…Our study also showed that mean particle circularity (roundness) was noticeably higher in the contemporary L-TDR cohort (mean, 0.8 versus mean, 0.4), but aspect ratios were within the same range as those of historical L-TDR particles [28]. Interestingly, UHMWPE particles from conventional THAs fabricated with c-inert-sterilized UHMWPE acetabular liners have been reported to have shapes similar to the contemporary L-TDR group [3,[10][11][12]23]. Multiple studies have reported that particles with more rounded morphologies trigger less robust macrophage activation compared with fibrillar-shaped particles [11,31,37].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our study also showed that mean particle circularity (roundness) was noticeably higher in the contemporary L-TDR cohort (mean, 0.8 versus mean, 0.4), but aspect ratios were within the same range as those of historical L-TDR particles [28]. Interestingly, UHMWPE particles from conventional THAs fabricated with c-inert-sterilized UHMWPE acetabular liners have been reported to have shapes similar to the contemporary L-TDR group [3,[10][11][12]23]. Multiple studies have reported that particles with more rounded morphologies trigger less robust macrophage activation compared with fibrillar-shaped particles [11,31,37].…”
Section: Discussionsupporting
confidence: 57%
“…Initial validation of this technique was performed using an environmental scanning electron microscope (ESEM) to study histomorphologic changes and wear debris in periprosthetic tissues of THAs [2]. Particle size and shape were characterized by measuring the equivalent circular diameter (ECD), perimeter-based-circularity, and aspect ratio as described in an earlier study by Baxter et al [3].…”
Section: Wear Particle Characterizationmentioning
confidence: 99%
“…7 The more wear resistant HXLPE has, in recent years, been the most implanted polyethylene type in several countries. [7][8][9] Its debris is similar in size and shape to the conventional UHMWPE, [10][11] however the reduction in wear volume by an order of magnitude could reduce the secondary effects.…”
Section: Introductionmentioning
confidence: 99%
“…Early in vitro assessments of the inflammatory potential of highly crosslinked UHMWPE suggested that the particles might be more stimulatory of inflammatory cytokine production [37], but clinical data have not confirmed this observation. Baxter et al [9,10] observed the presence of necrosis associated with small wear particles was a dominant histomorphologic change in noncapsular tissues from failed highly crosslinked UHMWPE implants but noted that the quantity of UHMWPE wear debris, and consequently the presence of histiocytes, giant cells, and necrosis, was significantly lower in the highly crosslinked UHMWPE tissues. Inflammatory reactions in tissues containing highly crosslinked UHMWPE debris were reported to be mild and significantly reduced compared with the macrophage responses in response to conventional UHMWPE particles [10].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Baxter et al [9,10] observed the presence of necrosis associated with small wear particles was a dominant histomorphologic change in noncapsular tissues from failed highly crosslinked UHMWPE implants but noted that the quantity of UHMWPE wear debris, and consequently the presence of histiocytes, giant cells, and necrosis, was significantly lower in the highly crosslinked UHMWPE tissues. Inflammatory reactions in tissues containing highly crosslinked UHMWPE debris were reported to be mild and significantly reduced compared with the macrophage responses in response to conventional UHMWPE particles [10]. Higher numbers of T lymphocytes were also observed in pseudocapsules from conventional UHMWPE when compared with highly crosslinked UHMWP [45], leading to the overall impression that the use of highly crosslinked UHMWPE has the potential to reduce the potential development of osteolysis.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%